Correlation between Glycemic Control in Type 2 Diabetes Mellitus Patients with Natural Killer Cell Activity - Dian Ristanti; Gatot Soegiarto; Hermina Novida (Jurnal Penyakit Dalam Indonesia)
Introduction. Most of the previous studies showed decreased polymorphonuclear cells and monocytes/macrophages in type 2 diabetes mellitus (T2DM). Natural killer (NK) cell functions were rarely studied in T2DM. This study aimed to evaluate NK cell activity and determine its correlation with glycemic control in T2DM patients.